Results of multimodality treatment with promisan incorporated into its regimen for patients with disseminated ovarian cancer - A. V. Zharov; G. R. Kravchenko; L. F. Chernova; T. N. Gubaidullina (Опухоли женской репродуктивной системы, 2014)
The problem of ovarian cancer (OC) is considered. The efficiency of multimodality treatment with and without promisan incorporated into its regimen was evaluated in 2 groups of patients with disseminated OC. The efficacy and tolerance of promisan used in patients with disseminated OC are analyzed.А.В. Жаров, Г.Р. Кравченко, Л.Ф. Чернова, Т.Н. ГубайдуллинаЧелябинский окружной клинический онкологический диспансер Контакты: Александр Владимирович Жаров roc_chel@mail.ru